VT arising from sub‐aortic muscular outflow tract structures: In two patients with ventricular septal defects. Issue 8 (13th April 2019) - Chang, Shu; Marzec, Lucas; Kay, Joseph; Khanna, Amber; Sauer, William H.; Nguyen, Duy T.
Abstract: Background: Outflow tract ventricular tachycardias (OTVT) most commonly occur in the absence of structural abnormalities. We present two cases in which a structural variant in the outflow tract was critical to the OTVT. Cases: Subaortic muscular bands were identified using intracardiac echocardiography (ICE) in each of our cases with history of VSD and VT. Mapping demonstrating their critical involvement to the tachycardia and ablation along the muscular bands rendered the ventricular tachycardias non‐inducible. Conclusion: In rare instances, a structural variant may be involved in OTVTs. The use of ICE along with electroanatomic mapping can assist in successful ablation of these ventricular tachycardias.